Roadkills in Northern Peninsular Malaysia - Hui, Tabitha C. Y.; Slade, Eleanor M.; Chong, Ju Lian (Frontiers in Environmental Science, 2021)
As Malaysia’s economy continues to grow, an ever-expanding road network is being built to support the new developments. Whilst roads increase accessibility to Malaysia’s resource rich rural areas, they also bring with them a host of environmental problems such as destruction and fragmentation of habitat, poaching, pollution and roadkills. Of these, roadkills are the most direct and visible impact of building roads, yet few dedicated studies have been conducted on the extent of roadkills and how to minimize them in Malaysia. In this study, we examined the species richness and abundance of vertebrate roadkills along eight one-km stretches (two in each habitat) of highways in Terengganu and Pahang across four habitat types: rainforest, oil palm plantation, subsistence agricultural land, and village. Each stretch of highway was surveyed by walking it six times between May to October 2017 for the Terengganu segments and May to October 2018 for the Pahang segments. A total of 305 roadkilled animals were recorded, consisting of at least 24 species. Three of these are protected by Malaysian law. The most common roadkilled animals were frogs (102 individuals) followed by birds (70 individuals), mammals (67 individuals) and reptiles (66 individuals). The highest number of roadkills were recorded in roads going through villages (112 individuals), followed by oil palm plantations (81 individuals), forests (65 individuals) and subsistence agricultural land (47 individuals). For every roadkill we also recorded the location’s specific habitat and landscape characteristics such as distance to the nearest fruit tree, tree, shrub, water body, human structure, and overhead cable. Most roadkills were found close to vegetation cover and water bodies. However, we found that roadkills decreased to near zero between 30-80 m from the nearest shrub or tree. Roadkills decreased over larger distances from the nearest water body, but in oil palm and village habitats, reducing water bodies within 20-50 m from a road would almost half the number of roadkills. We suggest that making changes to the structure and composition of roadside vegetation and other landscape features, such as thinning vegetation to discourage wildlife from gathering near roads, could significantly reduce the number of roadkills.